Digital Technologies and Applications Proceedings of ICDTA’22, Fez, Morocco, Volume 1 - Motahhir, Saad; Bossoufi, Badre (Lecture Notes in Networks and Systems, 2022)
XVI, 858 p. 531 illus., 408 illus. in color.